The Mark of the Beast, Revelation 13:16 - Judge, Edwin A. (Tyndale bulletin, 1991)
A mark on the hand or forehead permits admission to the market in Rev. 13:16; is this an imaginary scene, or can one envisage actual market control practices using marks?